2013
DOI: 10.1088/0957-4484/24/21/215202
|View full text |Cite
|
Sign up to set email alerts
|

Crystal phase engineered quantum wells in ZnO nanowires

Abstract: We report the fabrication of quantum wells in ZnO nanowires (NWs) by crystal phase engineering approach. Basal plane stacking faults (BSF) in wurtzite structure can be considered as a minimal segment of zinc blende. Due to the existing band offsets at wurtzite (WZ) / zinc blende (ZB) materials interface incorporation of BSF of high density into ZnO NWs results in type II band alignment. Thus, the BSF structure acts as a quantum well for electrons and a potential barrier for holes in the valence band.We have st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(45 reference statements)
0
13
1
Order By: Relevance
“…33 Also reported recently is the formation of a quantum wire at the intersection between a 3.8 nm thick (Al,Ga)N/GaN quantum well and BSFs, leading to radiative recombination of localized excitons. 34 Although the energetic position reported by Khranovskyy et al 5 is considerably higher than what has been reported by Schirra et al, 29 Thonke et al 30 and also in this work, Khranovskyy et al 5 clearly demonstrated the presence of a high density of BSFs perpendicular to the c-axis. They also studied temperature and laser power dependent PL and concluded that the line has an excitonic nature.…”
Section: Figurecontrasting
confidence: 41%
See 4 more Smart Citations
“…33 Also reported recently is the formation of a quantum wire at the intersection between a 3.8 nm thick (Al,Ga)N/GaN quantum well and BSFs, leading to radiative recombination of localized excitons. 34 Although the energetic position reported by Khranovskyy et al 5 is considerably higher than what has been reported by Schirra et al, 29 Thonke et al 30 and also in this work, Khranovskyy et al 5 clearly demonstrated the presence of a high density of BSFs perpendicular to the c-axis. They also studied temperature and laser power dependent PL and concluded that the line has an excitonic nature.…”
Section: Figurecontrasting
confidence: 41%
“…These planar inclusions of ZB ZnO in the normal WZ crystal have been theoretically shown to form type-II QWs with a valence/conduction band offset of 37/147 meV. 33 The insertions of such regions result from the formation of BSFs perpendicular to the c-axis, as experimentally observed by Khranovskyy et al 5 Theoretically, electrons are weakly confined in the well and the holes are located in the barriers of these structures. 33 Also reported recently is the formation of a quantum wire at the intersection between a 3.8 nm thick (Al,Ga)N/GaN quantum well and BSFs, leading to radiative recombination of localized excitons.…”
Section: Figurementioning
confidence: 79%
See 3 more Smart Citations